PENENTUAN FREKUENSI PEMESANAN KOMPONEN LENSA KAMERA MENGGUNAKAN METODE DETERMINISTIK DINAMIS UNTUK MEMINIMALISASI BIAYA PERSEDIAAN PADA PT XACTI INDONESIA - Lisa Hadiyanti; M Tirtana Siregar (Jurnal Manajemen Industri dan Logistik, 2018)
This study aims to determine the comparison of order determination on camera lens components and the costs incurred between company policies and dynamic deterministic methods. This study uses dynamic deterministic methods, namely Wagner-Whitin Algorithm, Silver Meal, Least Unit Cost, Economic Part Period, Lot For Lot and Least Total Cost to determine the amount of costs incurred by the company each time the order on the camera lens component. Of all these dynamic deterministic methods, the most efficient is the Wagner-Whitin Algorithm method with an order frequency of 10 times the order and the cost incurred is Rp. 34,529,190. The Silver Meal method with the order frequency of 10 times the order and the cost incurred is Rp. 35,390,310. Least Unit Cost method with the order frequency of 10 times the order and the cost incurred is Rp. 35,234,830. The method of the Economic Part Period with an order frequency of 10 times the order and costs incurred in the amount of Rp. 35,390,310. Method Lot For Lot with the order frequency of 12 times the order and the cost incurred is Rp. 36,720,396. And the Least Total Cost with the order frequency of 10 times the order and the cost incurred is Rp. 35,390,310. In company policy, 12 orders are made at a cost of Rp. 36,720,396. So that the proposed improvement can be given is that the company is expected to use the Wagner-Whitin Algorithm method which has a minimum order frequency and cost.